2001
DOI: 10.1034/j.1600-079x.2001.310212.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against oxidative mitochondrial damage induced in rat placenta by ischemia and reperfusion

Abstract: We assessed the effects of melatonin, a powerful scavenger of oxygen free radicals, on ischemia/reperfusion-induced oxidative damage to mitochondria in the rat placenta. In Wistar rats at day 19 of pregnancy, feto-placental ischemia was induced by occluding both utero-ovarian arteries for 20 min. Reperfusion was achieved by releasing the occlusion and restoring circulation for 30 min. Melatonin solution or the vehicle alone was injected intraperitoneally at dose of 10 mg/kg 1 hr before occlusion. Sham-ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 21 publications
0
48
0
2
Order By: Relevance
“…Also in vivo, acute administration of aMT protected diaphragmatic and skeletal muscle mitochondria from oxidative/nitrosative damage (Escames et al 2006, Lopez et al 2006b), improving the ability of these mitochondria to produce ATP (Lopez et al 2006a). In SAM mice, aMT administration counteracted mitochondrial deficiencies (Okatani et al 2001(Okatani et al , 2002a. Recently, an inverse relationship was demonstrated between the reduction in aMT content and the increased oxidative damage in several tissues of SAM mice including liver, spleen and thymus (Lardone et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Also in vivo, acute administration of aMT protected diaphragmatic and skeletal muscle mitochondria from oxidative/nitrosative damage (Escames et al 2006, Lopez et al 2006b), improving the ability of these mitochondria to produce ATP (Lopez et al 2006a). In SAM mice, aMT administration counteracted mitochondrial deficiencies (Okatani et al 2001(Okatani et al , 2002a. Recently, an inverse relationship was demonstrated between the reduction in aMT content and the increased oxidative damage in several tissues of SAM mice including liver, spleen and thymus (Lardone et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin reduces lipid peroxidation and protects against I/R injury through its radical-scavenging action [13][14][15][16][17]. It is nontoxic, rapidly absorbed from any tissue, and diffuses easily through interstitial and cell compartments alike.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that acute aMT administration, an antioxidant and free radical scavenger (Antolin et al, 1996;Tan et al, 2000aTan et al, , 2000bTan et al, , 2002Turjanski et al, 2001), counteracted mitochondrial deficiencies in SAM mice (Okatani et al, 2001(Okatani et al, , 2002a(Okatani et al, , 2002b. The indoleamine and several of its metabolites are scavengers of free radicals and it is now considered a component of the endogenous antioxidant system (Reiter, 1998(Reiter, , 2000Tan et a., 2007).…”
mentioning
confidence: 99%